Assessing the AQS/TAS-45 Indonesia Version for Children Attachment in Yogyakarta (Journal of Educational, Health and Community Psychology, 2012)
The  purpose  of  this  study  was  to  examine  the  Indonesia  versions  of  the  Attachment  Q-Sort/AQS-Toddler  Attachment  Sort-45/TAS-45  (Bimler  &  Kirkland,  2002).  Assessing  the  children  attachment in  Indonesia  has  not  been  done  lately.  Data  were  collected  through  observation  of  84  Indonesian toddlers  residing  in  Yogyakarta.  The  validity  of  the  TAS-45  was  determined  by  Kirkland  (2008) through  mapping  TAS-45  for  the  Indonesian  users.  This  study  had  the  inter-rater  reliability  of  0.92 that indicated the convincing score. Study finding shows the Indonesian AQS/TAS-45 is reliable and valid in  for Indonesia children sample and suggest that the TAS-45 Indonesia  version reflect similar concept to those in the original English versions. Keywords: AQS/TAS-45, Child, Attachment